Leaf nutrients in Prosopis pallida are determined by soil chemical attributes under eutric conditions in a dryland forest - Salazar P.C. (2021)
Key message: Soil pH, EC, and salinity explain the leaf nutrient concentrations of Prosopis pallida despite the high amount of soil nutrients near the trees. Abstract: Dryland forests constantly face extreme abiotic conditions, and this affects plant growth and nutrition. We have determined the effects of soil chemical attributes and soil nutrients on the leaf nutrient concentrations of eight Prosopis pallida populations located along a climatic gradient in the North-Peruvian dryland forests. We analyzed the leaf chemical composition (N, P, K, Ca, Mg, Fe, Mn, Cu, and Zn), as well as soil chemical attributes [texture, pH, salinity (electrical conductivity; EC), and the sodium adsorption ratio (SAR)] and soil nutrient concentrations (the same elements as in the leaves) at 2 m from the base of each tree. The soil and leaf nutrient concentrations were not associated with the climatic gradient and were highly variable within populations. Despite the dry conditions, the soil nutrients were not a limiting resource (eutric conditions), and thus the soil chemical attributes were the main driver of the variation in leaf nutrient concentrations. Interestingly, leaf Mn was correlated with soil and leaf nutrients, as well as with soil chemical attributes, suggesting it can be used as an early indicator of plant nutrition. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.